A self-healing network polymer electrolyte and its preparation method and application, polymer lithium battery
By using the self-healing mesh polymer electrolyte in the lithium battery, the use of sulfurnol-elene clicks to react to form a dynamic sulfur bond network structure, solving the problem of poor flexibility and low energy density in traditional lithium batteries in wearable devices. High -conductive rates and self -healing functions have improved the cycle performance and magnification performance of the battery.
Patent Information
- Application Number
- CN202211719056.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-30
Smart Images

Figure CN115954539B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer lithium batteries, and in particular to a self-healing network polymer electrolyte, a preparation method and application thereof, and a polymer lithium battery. Background Art
[0002] Wearable electronic devices such as smart bracelets and smart glasses are becoming more and more popular. However, traditional lithium batteries are difficult to use in wearable devices due to their poor flexibility and low energy density. Therefore, researchers have extensively studied flexible solid-state lithium batteries with high energy density and good flexibility to meet consumer demand for wearable devices. As a key component of flexible lithium batteries, solid electrolytes are inevitably subjected to external forces such as stretching, twisting and bending in practical applications, resulting in microcracks and fractures, which hinder the transmission of lithium ions inside the solid electrolyte and seriously affect the performance and cycle performance of solid electrolyte batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a self-healing network polymer electrolyte and its preparation method and application, and a polymer lithium battery. The self-healing network polymer electrolyte has high conductivity at room temperature, stable interface contact and can achieve self-healing without external stimulation.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a self-healing network polymer electrolyte, which comprises the following raw materials, measured by weight: 3 to 10 parts of ionic liquid, 40 to 70 parts of polyethylene glycol diacrylate, 1 to 10 parts of disulfide diacrylate, 1 to 5 parts of crosslinking agent, 3 to 10 parts of chain extender, 1 to 5 parts of alkali, 20 to 30 parts of lithium salt, 1 to 10 parts of photoinitiator and 90 to 110 parts of solvent;
[0006] The cross-linking agent and the chain extender both include mercapto groups.
[0007] Preferably, the ionic liquid includes one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 2,3-dimethyl-1-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-1-methylpiperidinium bis(trifluoromethanesulfonyl)imide and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0008] Preferably, the disulfide diacrylate includes bis(4-vinylphenyl) disulfide and / or disulfide dimethacrylate.
[0009] Preferably, the crosslinking agent includes one or more of tetrakis(3-mercaptopropionate)pentaerythritol, hexa(3-mercaptopropionate)dipentaerythritol and trimethylolpropane tris(3-mercaptopropionate).
[0010] Preferably, the chain extender includes one or more of 3,6-dioxa-1,8-octanedithiol, 1,8-octanedithiol, 1,10-decandithiol, 1,4-butanedithiol, 1,2-ethanedithiol, 1,16-hexadecandithiol, 1,5-pentanedithiol and 1,6-hexanedithiol;
[0011] The photoinitiator includes one or more of 2,2-dimethoxy-2-phenylacetophenone, 4-methylbenzophenone and 1-hydroxycyclohexylphenyl ketone.
[0012] Preferably, the base comprises one or more of n-butylamine, tert-butylamine, n-propylamine, tert-amylamine and isobutylamine;
[0013] The lithium salt includes one or more of LiPF6, LiClO4, LiTFSI, LiFSI, LiBOB and LiDFOB.
[0014] The present invention also provides a method for preparing the self-healing network polymer electrolyte described in the above technical solution, comprising the following steps:
[0015] The ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, a crosslinking agent, a chain extender, a lithium salt and a solvent are mixed, and then mixed with a photoinitiator and a base to obtain a precursor solution;
[0016] The precursor solution is UV cured to obtain the self-healing network polymer electrolyte.
[0017] Preferably, the UV curing irradiation wavelength is 100-380 nm, and the irradiation light intensity is 10-200 mW·cm -2 , time is 0.5 to 10 hours.
[0018] The present invention also provides the use of the self-healing network polymer electrolyte described in the above technical solution or the self-healing network polymer prepared by the preparation method described in the above technical solution in a polymer lithium battery.
[0019] The present invention also provides a polymer lithium battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the self-healing network polymer electrolyte described in the above technical solution or the self-healing network polymer prepared by the preparation method described in the above technical solution.
[0020] The present invention provides a self-healing network polymer electrolyte, which includes the following raw materials by weight: 3-10 parts of ionic liquid, 40-70 parts of polyethylene glycol diacrylate, 1-10 parts of disulfide diacrylate, 1-5 parts of cross-linking agent, 3-10 parts of chain extender, 1-5 parts of alkali, 20-30 parts of lithium salt, 1-10 parts of photoinitiator and 90-110 parts of solvent; the cross-linking agent and chain extender both include thiol. A thiol-ene click reaction occurs between the carbon-carbon double bonds in the disulfide diacrylate and polyethylene glycol diacrylate and the thiol groups of the cross-linking agent and the chain extender, so that the self-healing network polymer electrolyte has a disulfide bond network structure, and the dynamic disulfide bonds can enable the electrolyte membrane to achieve self-healing at room temperature without external stimulation. The ionic liquid has good ion transport and flame retardancy, which not only accelerates the transmission of lithium ions but also has good flame retardancy. It improves the conductivity of the electrolyte membrane at room temperature without reducing the mechanical properties of the membrane, and the electrolyte membrane has good interface compatibility with the lithium metal negative electrode, which reduces the impedance of the interface, thereby improving the cycle performance and rate performance of the battery. According to the records in the examples, the ionic conductivity of the self-healing network polymer electrolyte of the present invention reaches 1.13×10 -4 S cm -1 The lithium iron phosphate battery assembled using the self-healing network polymer electrolyte as the electrolyte has a discharge capacity of 160 mAh g at a rate of 0.1C. -1 .
[0021] The present invention also provides a method for preparing the self-healing network polymer electrolyte described in the above technical solution, comprising the following steps: mixing an ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, a crosslinking agent, a chain extender, a lithium salt and a solvent, and then mixing with a photoinitiator and a base to obtain a precursor solution; UV curing the precursor solution to obtain the self-healing network polymer electrolyte. The UV curing can promote the occurrence of a thiol-ene click reaction; and the preparation method is simple to operate, mild in conditions and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The infrared spectra of the self-healing network polymer electrolyte, pentaerythritol tetrakis(3-mercaptopropionic acid), polyethylene glycol diacrylate, diphenyl disulfide bis(2-methylacrylamide) and 3,6-dioxa-1,8-octanedithiol obtained in Example 1;
[0023] Figure 2 The physical picture and SEM picture of the self-healing network polymer electrolyte prepared in Example 1;
[0024] Figure 3The graph of ionic conductivity variation with temperature of the self-healing network polymer electrolyte membrane prepared in Example 1 and the self-healing network polymer electrolyte membrane after self-healing for 24 hours;
[0025] Figure 4 This is a room temperature cycle test diagram of a button cell assembled with the self-healing network polymer electrolyte prepared in Example 1 as the electrolyte;
[0026] Figure 5 This is a room temperature rate cycle test diagram of the button cell described in Example 1;
[0027] Figure 6 Cyclic stability curve of Li / / Li symmetric button cell assembled with self-healing network polymer electrolyte prepared in Example 1;
[0028] Figure 7 The self-healing process of the self-healing network polymer electrolyte membrane prepared in Example 1 at room temperature;
[0029] Figure 8 This is the flame retardant process of the self-healing network polymer electrolyte membrane prepared in Example 1. DETAILED DESCRIPTION
[0030] The present invention provides a self-healing network polymer electrolyte, which comprises the following raw materials, measured by weight: 3 to 10 parts of ionic liquid, 40 to 70 parts of polyethylene glycol diacrylate, 1 to 10 parts of disulfide diacrylate, 1 to 5 parts of crosslinking agent, 3 to 10 parts of chain extender, 1 to 5 parts of alkali, 20 to 30 parts of lithium salt, 1 to 10 parts of photoinitiator and 90 to 110 parts of solvent;
[0031] The cross-linking agent and the chain extender both include mercapto groups.
[0032] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0033] In terms of mass fractions, the raw materials for preparing the self-healing network polymer electrolysis of the present invention include 3 to 10 parts of ionic liquid, preferably 4 to 8 parts, and more preferably 5 to 6 parts. In the present invention, the ionic liquid preferably includes one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium tetrafluoroboric acid, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 2,3-dimethyl-1-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-1-methylpiperidinium bis(trifluoromethanesulfonyl)imide and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; more preferably 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; when the ionic liquid is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio.
[0034] In the present invention, the ionic liquid not only accelerates the transmission of lithium ions but also has good flame retardancy, improves the conductivity of the electrolyte membrane at room temperature without reducing the mechanical properties of the membrane, and has good interface compatibility between the electrolyte membrane and the lithium metal negative electrode, reduces the impedance of the interface, thereby improving the cycle performance and rate performance of the battery.
[0035] Based on the mass fraction of the ionic liquid, the raw material for preparing the self-healing network polymer electrolysis of the present invention includes 40 to 70 parts of polyethylene glycol diacrylate, preferably 45 to 65 parts, and more preferably 50 to 60 parts. In the present invention, the molecular weight of the polyethylene glycol diacrylate is preferably 400 to 4000 g / mol, more preferably 1000 to 3000 g / mol. In the present invention, the role of the polyethylene glycol diacrylate is to transport lithium ions and improve the mechanical properties of the self-healing network polymer electrolysis.
[0036] Based on the mass fraction of the ionic liquid, the raw material for preparing the self-healing network polymer electrolysis of the present invention includes 1 to 10 parts of disulfide diacrylate, preferably 2 to 8 parts, and more preferably 4 to 6 parts. In the present invention, the disulfide diacrylate preferably includes bis(4-vinylphenyl) disulfide and / or disulfide dimethacrylate, more preferably disulfide dimethacrylate.
[0037] In the present invention, the preparation method of disulfide dimethacrylate preferably comprises the following steps:
[0038] In a nitrogen atmosphere, disulfide, isocyanoethyl methacrylate and an organic solvent are mixed and reacted to obtain the disulfide dimethacrylate.
[0039] In the present invention, the nitrogen atmosphere is preferably achieved by bubbling with nitrogen.
[0040] In the present invention, the disulfide preferably includes one or more of 4,4-diaminodiphenyl disulfide, bis(4-hydroxyphenyl) disulfide, bis(2-hydroxyethyl) disulfide and bis(2-diaminoethyl) disulfide; when the disulfide is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the organic solvent preferably includes one or more of benzene, toluene, dichloromethane, methanol, ethanol, acetone, acetonitrile, dimethyl sulfoxide and N,N-dimethylformamide; when the organic solvent is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, when the disulfide is 4,4-diaminodiphenyl disulfide or bis(2-diaminoethyl) disulfide, the reaction does not require the addition of a catalyst; when the disulfide is bis(4-hydroxyphenyl) disulfide or bis(2-hydroxyethyl) disulfide, the reaction requires the addition of a catalyst, and the catalyst is preferably dibutyltin dilaurate; the mass ratio of the disulfide to the volume of the dibutyltin dilaurate is 2.5g:1mL or 0.31g:0.2mL.
[0041] In the present invention, the mass ratio of the disulfide, isocyanoethyl methacrylate and the organic solvent is preferably (3-10):(5-10):(5-15).
[0042] The present invention has no special limitation on the mixing, and the mixing may be carried out by a process well known to those skilled in the art and ensure that the disulfide and isocyanoethyl methacrylate can be fully dissolved in the organic solvent.
[0043] In the present invention, the reaction temperature is preferably 20 to 80°C, more preferably 30 to 60°C, and most preferably 40 to 50°C; the reaction time is preferably 10 to 30 hours, and more preferably 15 to 25 hours. In the present invention, the reaction is preferably carried out under stirring conditions, and the present invention does not have any special restrictions on the stirring conditions, and the conditions well known to those skilled in the art can be used.
[0044] In the present invention, the role of the disulfide diacrylate is that the dynamic disulfide bonds contained therein can enable the electrolyte membrane to achieve self-healing at room temperature without external stimulation.
[0045] Based on the mass fraction of the ionic liquid, the raw material for preparing the self-healing network polymer electrolysis of the present invention includes 1 to 5 parts of a cross-linking agent, preferably 2 to 4 parts, and more preferably 2.5 to 3.5 parts. In the present invention, the cross-linking agent preferably includes one or more of tetrakis(3-mercaptopropionic acid) pentaerythritol ester, hexa(3-mercaptopropionic acid) dipentaerythritol ester and trimethylolpropane tris(3-mercaptopropionate); when the cross-linking agent is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0046] In the present invention, the role of the crosslinking agent is to generate a self-healing network polymer through a thiol-ene click reaction between the carbon-carbon double bonds of disulfide diacrylate and polyethylene glycol diacrylate and the thiol group of the crosslinking agent, thereby improving the mechanical properties of the polymer.
[0047] Based on the mass fraction of the ionic liquid, the raw materials for preparing the self-healing network polymer electrolysis of the present invention include 3 to 10 parts of chain extenders, preferably 4 to 8 parts, and more preferably 5 to 6 parts. In the present invention, the chain extender preferably includes one or more of 3,6-dioxa-1,8-octanedithiol, 1,8-octanedithiol, 1,10-decanthiol, 1,4-butanedithiol, 1,2-ethanedithiol, 1,16-hexadecanedithiol, 1,5-pentanedithiol and 1,6-hexanedithiol; when the chain extender is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio.
[0048] In the present invention, the role of the chain extender is to polymerize the disulfide diacrylate and polyethylene glycol diacrylate with the chain extender through a thiol-ene click reaction between the carbon-carbon double bonds of the disulfide diacrylate and polyethylene glycol diacrylate and the thiol group of the chain extender, thereby increasing the length of the molecular chain segment and improving the flexibility of the polymer.
[0049] Based on the mass fraction of the ionic liquid, the raw materials for preparing the self-healing network polymer electrolysis of the present invention include 1 to 5 parts of alkali, preferably 2 to 5 parts, and more preferably 3 to 4 parts. In the present invention, the alkali preferably includes one or more of n-butylamine, tert-butylamine, n-propylamine, tert-amylamine and isobutylamine; when the alkali is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0050] In the present invention, the base functions to accelerate the reaction between the carbon-carbon double bond and the thiol group.
[0051] Based on the mass fraction of the ionic liquid, the raw materials for preparing the self-healing network polymer electrolyte of the present invention include 20 to 30 parts of lithium salt, preferably 22 to 28 parts, and more preferably 23 to 26 parts. In the present invention, the lithium salt preferably includes one or more of LiPF6, LiClO4, LiTFSI, LiFSI, LiBOB and LiDFOB; when the lithium salt is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.
[0052] In the present invention, the lithium salt functions to provide lithium ions and lower the glass transition temperature of the polymer electrolyte.
[0053] Based on the mass fraction of the ionic liquid, the raw materials for preparing the self-healing network polymer electrolyte of the present invention include 1 to 10 parts of photoinitiator, preferably 2 to 8 parts, and more preferably 3 to 6 parts. In the present invention, the photoinitiator preferably includes one or more of 2,2-dimethoxy-2-phenylacetophenone, 4-methylbenzophenone and 1-hydroxycyclohexylphenyl ketone; when the photoinitiator is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0054] Based on the mass fraction of the ionic liquid, the raw material for preparing the self-healing network polymer electrolysis of the present invention includes 90 to 110 parts of solvent, preferably 95 to 105 parts, and more preferably 98 to 102 parts. In the present invention, the solvent is preferably anhydrous acetonitrile.
[0055] In the present invention, the shape of the self-healing network polymer electrolyte is preferably a self-healing network polymer electrolyte membrane, and the thickness of the self-healing network polymer electrolyte membrane is preferably 100 to 120 μm.
[0056] The present invention also provides a method for preparing the self-healing network polymer electrolyte described in the above technical solution, comprising the following steps:
[0057] The ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, a crosslinking agent, a chain extender, a lithium salt and a solvent are mixed, and then mixed with a photoinitiator and a base to obtain a precursor solution;
[0058] The precursor solution is UV cured to obtain the self-healing network polymer electrolyte.
[0059] The ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, a crosslinking agent, a chain extender, a lithium salt and a solvent are mixed, and then mixed with a photoinitiator and a base to obtain a precursor solution.
[0060] In the present invention, the mixing of the ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, crosslinking agent, chain extender, lithium salt and solvent is preferably carried out under stirring; the stirring time is preferably 5 to 12 hours. The present invention does not have any special limitation on the stirring speed. The speed familiar to those skilled in the art is adopted and the ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate, crosslinking agent, chain extender and lithium salt are fully dissolved in the solvent under the above stirring time.
[0061] In the present invention, the mixing with the photoinitiator and the base is preferably carried out under stirring; the stirring time is preferably 2 to 5 hours. The present invention does not have any special limitation on the stirring speed. A speed familiar to those skilled in the art can be used to ensure that the photoinitiator and the base are fully dissolved in the solvent under the above stirring time.
[0062] After obtaining the precursor solution, the present invention performs UV curing on the precursor solution to obtain the self-healing network polymer electrolyte.
[0063] After obtaining the precursor solution, the present invention also preferably performs ultrasonic treatment on the precursor solution for 1 to 10 minutes. The present invention does not have any special limitation on the conditions of the ultrasonic treatment, and the conditions well known to those skilled in the art can be used.
[0064] After the ultrasonic treatment is completed, the present invention also preferably includes scraping the precursor solution on the surface of the polytetrafluoroethylene plate and then pre-curing. In the present invention, the scraping is preferably done by a scraper with a groove of 750 μm; the pre-curing method is preferably drying, the drying temperature is preferably 20 to 40° C., and the drying time is preferably 20 to 40 hours.
[0065] In the present invention, the UV curing irradiation wavelength is preferably 100 to 380 nm, more preferably 300 to 380 nm; the irradiation light intensity is preferably 10 to 200 mW·cm -2 , more preferably 100 to 200 mW·cm -2 ; The time is preferably 0.5 to 10 hours, more preferably 0.5 to 1.5 hours.
[0066] After the UV curing is completed, the present invention preferably further includes vacuum drying; the present invention has no special limitation on the process of vacuum drying, and a process well known to those skilled in the art can be used. After the vacuum drying is completed, the present invention preferably further includes film peeling; the present invention has no special limitation on the process of film peeling, and a process well known to those skilled in the art can be used.
[0067] The present invention also provides the use of the self-healing network polymer electrolyte described in the above technical solution or the self-healing network polymer prepared by the preparation method described in the above technical solution in a polymer lithium battery.
[0068] The present invention also provides a polymer lithium battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that the electrolyte is the self-healing network polymer electrolyte described in the above technical solution or the self-healing network polymer prepared by the preparation method described in the above technical solution.
[0069] The present invention has no special requirements for the positive electrode and the negative electrode, and the positive electrode and the negative electrode for lithium electrode well known to those skilled in the art can be used. In a specific embodiment of the present invention, the positive electrode includes a positive electrode active material, a current collector, a conductive agent and a binder, and the mass ratio of the positive electrode active material, the conductive agent and the binder is preferably 8:1:1; the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and lithium iron manganese phosphate; the current collector preferably includes copper foil or aluminum foil; the conductive agent preferably includes one or more of acetylene black, Ketjen black and carbon nanotubes; the binder preferably includes one or more of polytetrafluoroethylene, polyurethane and polyvinylidene fluoride. In the present invention, the negative electrode is preferably metallic lithium. The present invention has no special requirements for the assembly method of the polymer lithium battery, and the assembly method well known to those skilled in the art can be used.
[0070] The polymer lithium battery provided by the present invention uses the self-healing network polymer electrolyte as an electrolyte and has excellent rate performance.
[0071] The self-healing network polymer electrolyte, preparation method and application thereof, and polymer lithium battery provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0072] Example 1
[0073] Dissolve 2.5 g of 4,4-diaminodiphenyl disulfide in acetone, add 2.9 mL of methyl methacrylate isocyanoethyl ester after nitrogen bubbling for 30 min, and stir at room temperature for 20 h to obtain diphenyl disulfide bis(2-methylacrylamide);
[0074] 0.55 g of lithium salt (LiTFSI), 0.08 g of ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide salt), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of diphenyl disulfide bis(2-methylacrylamide), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0075] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), after curing, drying in a vacuum oven at 60° C. for 4 h, peeling off the film, and obtaining a self-healing network polymer electrolyte;
[0076] Figure 1 The infrared spectra of the self-healing network polymer electrolyte obtained in Example 1, pentaerythritol tetrakis(3-mercaptopropionic acid), polyethylene glycol diacrylate, diphenyl disulfide bis(2-methylacrylamide) and 3,6-dioxa-1,8-octanedithiol, wherein 2560 cm -1 Absorption band V S-H Peak and 1620cm -1 Absorption band V C=C disappearance, indicating that pentaerythritol tetrakis(3-mercaptopropionic acid), polyethylene glycol diacrylate, diphenyl disulfide bis(2-methylacrylamide) and 3,6-dioxa-1,8-octanedithiol underwent a thiol-ene click reaction to form a network polymer;
[0077] Figure 2 The actual image and SEM image of the self-healing network polymer electrolyte prepared in Example 1, wherein (a) is a photo of the electrolyte folded in half, (b) is a photo of the electrolyte laid flat, and (c) is a SEM image of the self-healing network polymer electrolyte; Figure 2 It can be seen that the self-healing network polymer electrolyte prepared in Example 1 is a transparent self-supporting electrolyte membrane, and can be restored after folding and rolling up. The overall morphology shows that the electrolyte membrane has excellent mechanical flexibility and is dense and non-porous at the microscopic level; it is conducive to the interface contact between the electrodes;
[0078] Figure 3The ionic conductivity of the self-healing network polymer electrolyte membrane prepared in Example 1 and the self-healing network polymer electrolyte membrane after standing for 24 hours of self-healing is changed with temperature. The membrane thickness is about 110 μm, and the original ionic conductivity at 28°C is 1.13×10 -4 S cm -1 The ionic conductivity of the self-healing network polymer electrolyte membrane after self-healing is 0.569×10 -4 S cm -1 The ionic conductivity of the self-healing network polymer electrolyte membrane after self-healing is slightly lower than the original ionic conductivity;
[0079] The button cell was assembled using the self-healing network polymer electrolyte prepared in Example 1 as the electrolyte, the positive electrode active material was lithium iron phosphate, the current collector was aluminum foil, the conductive agent was acetylene black, the binder was polytetrafluoroethylene; the negative electrode was metallic lithium. Figure 4 This is a room temperature cycle test diagram of a button cell. Figure 4 It can be seen that the original and self-healed button cells assembled by self-healing network polymer electrolytes have an initial discharge capacity of 146.9 mAh g at a rate of 0.1C. -1 , and maintained 161 mAh g after 19 cycles -1 , with a Coulombic efficiency of 99.8%. The initial discharge capacity of the battery assembled by the self-healing network polymer electrolysis after self-healing is 140.9 mAh g -1 , and maintained 161 mAh g after 19 cycles -1 , the Coulombic efficiency is 99.9%, which is comparable to the original battery (146.9mAh·g -1 ) is very close, and the specific capacity reaches 161 mAh g after 19 cycles. -1 However, the self-healed self-healing network polymer electrolytic assembled battery showed a higher discharge specific capacity than the original battery after 11 cycles, indicating that the repaired electrolyte membrane can still be effectively applied to lithium-ion batteries;
[0080] Figure 5 The room temperature rate cycle test diagram of the button battery is shown in FIG. Figure 5 It can be seen that at room temperature, the discharge capacity of lithium iron phosphate at a rate of 0.1C is 160 mAh g -1 ; The discharge capacity at 0.2C rate is 150mAh g -1 ; The discharge capacity at 0.5C rate is 130mAh·g -1 ; The discharge capacity at 1C rate is 100mAh g -1 At a rate of 2C, the specific capacity of lithium iron phosphate is 80 mAh g -1, and when the current rate is restored to the initial 0.1C, the discharge specific capacity is almost completely restored. It can be seen that the button cell has excellent rate performance;
[0081] Figure 6 Cyclic stability curve of Li / / Li symmetric button cell assembled with self-healing network polymer electrolyte prepared in Example 1. Using lithium foil with a diameter of 12 mm, at 0.05 mA cm -2 At a current density of , the symmetrical battery has a Li + Electroplating and one hour Li + During the stripping cycle, the negative voltage and positive voltage represent the electroplating of lithium ions and the stripping of lithium ions, respectively. After 120 hours of cycling, the positive voltage is still constant at 0.15V, indicating that the interface between the Li negative electrode and the electrolyte membrane is relatively stable and that it has excellent interfacial compatibility with the lithium negative electrode.
[0082] Figure 7 The self-healing process of the self-healing mesh polymer electrolyte membrane prepared in Example 1 at room temperature. The thickness of the electrolyte membrane is about 800 μm. The use of a thicker membrane is intended to improve the operability of the self-healing test. The membrane was cut into two pieces with a scalpel so that the two separated parts were in contact. After standing for 24 hours, the cut membrane healed. Although the gap did not completely disappear, the healed membrane could withstand a weight of 100 g without breaking. It exhibits good self-healing properties, and its self-healing ability is attributed to the urea groups and dynamic disulfide bonds in the polymer;
[0083] Figure 8 This is the flame retardant process of the self-healing network polymer electrolyte membrane prepared in Example 1. When there is no igniter after the burning membrane, no further combustion is observed and the flame will extinguish itself, which has good flame retardant properties.
[0084] Example 2
[0085] The preparation steps of the self-healing network polymer electrolyte are as follows:
[0086] Dissolve 2.5 g of bis(4-hydroxyphenyl) disulfide in dichloromethane, bubbling nitrogen for 30 min, heating and stirring at 60°C for 30 min, adding 1 mL of dibutyltin dilaurate and 2.9 mL of methyl methacrylate isocyanoethyl ester when the temperature drops to 40°C, and stirring at 40°C for 20 h to obtain diphenyl disulfide bis(2-methylacrylate);
[0087] 0.55 g of lithium salt (LiTFSI), 0.08 g of ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide salt), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of diphenyl disulfide bis(2-methylacrylate), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0088] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), and after curing, it was dried in a vacuum oven at 60°C for 4 h, and the film was peeled off to obtain a self-healing network polymer electrolyte.
[0089] The room temperature conductivity of the self-healing network polymer electrolyte prepared in Example 2 is 8.76×10 -5 S cm -1 .
[0090] Example 3
[0091] The preparation steps of the self-healing network polymer electrolyte are as follows:
[0092] Dissolve 0.31 g of bis(2-hydroxyethyl) disulfide in dichloromethane, bubble nitrogen for 30 min, heat and stir at 60°C for 30 min, add 0.2 mL of dibutyltin dilaurate and 0.58 mL of methyl methacrylate isocyanoethyl ester when the temperature drops to 40°C, and stir at 40°C for 20 h to obtain disulfide bis(2-methylacrylate);
[0093] 0.55 g of lithium salt (LiTFSI), 0.08 g of ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide salt), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of disulfide bis(2-methylacrylate), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0094] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), and after curing, it was dried in a vacuum oven at 60°C for 4 h, and the film was peeled off to obtain a self-healing network polymer electrolyte.
[0095] The room temperature conductivity of the self-healing network polymer electrolyte prepared in Example 3 is 8.56×10 -5 S cm -1 .
[0096] Example 4
[0097] The preparation steps of the self-healing network polymer electrolyte are as follows:
[0098] Dissolve 2.5 g of 4,4-diaminodiphenyl disulfide in acetone, add 2.9 mL of methyl methacrylate isocyanoethyl ester after nitrogen bubbling for 30 min, and stir at room temperature for 20 h to obtain diphenyl disulfide bis(2-methylacrylamide);
[0099] 0.6063 g of lithium salt (LiTFSI), 0.1586 g of ionic liquid (1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of diphenyl disulfide bis(2-methylacrylamide), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0100] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), and after curing, it was dried in a vacuum oven at 60°C for 4 h, and the film was peeled off to obtain a self-healing network polymer electrolyte.
[0101] The room temperature conductivity of the self-healing network polymer electrolyte prepared in Example 4 is 1.24×10 -4 S cm -1 .
[0102] Example 5
[0103] The preparation steps of the self-healing network polymer electrolyte are as follows:
[0104] Dissolve 2.5 g of 4,4-diaminodiphenyl disulfide in acetone, add 2.9 mL of methyl methacrylate isocyanoethyl ester after nitrogen bubbling for 30 min, and stir at room temperature for 20 h to obtain diphenyl disulfide bis(2-methylacrylamide);
[0105] 0.6650 g of lithium salt (LiTFSI), 0.2379 g of ionic liquid (1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of diphenyl disulfide bis(2-methylacrylamide), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0106] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), and after curing, it was dried in a vacuum oven at 60°C for 4 h, and the film was peeled off to obtain a self-healing network polymer electrolyte.
[0107] The room temperature conductivity of the self-healing network polymer electrolyte prepared in Example 5 is 1.31×10 -4 S cm -1 .
[0108] Comparative Example 1
[0109] The preparation steps of the self-healing network polymer electrolyte are as follows:
[0110] Dissolve 2.5 g of 4,4-diaminodiphenyl disulfide in acetone, add 2.9 mL of methyl methacrylate isocyanate after nitrogen bubbling for 30 min, and stir at room temperature for 20 h to obtain diphenyl disulfide bis(2-methylacrylamide);
[0111] 0.489 g of lithium salt (LiTFSI), 1.25 g of 1000 g / mol polyethylene glycol diacrylate, 0.077 g of diphenyl disulfide bis(2-methylacrylamide), 0.0305 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.23 g of 3,6-dioxa-1,8-octanedithiol were dissolved in anhydrous acetonitrile and stirred for 12 h. After stirring evenly, 20 mg of photoinitiator and 10 μL of n-butylamine were added and stirring was continued for 1 h to obtain a uniform precursor solution;
[0112] The homogeneous precursor solution was ultrasonicated for 3 min, and the obtained slurry was scraped onto a 10×20 cm rectangular polytetrafluoroethylene plate, pre-cured in a desiccator for 24 h, and then irradiated with ultraviolet light for 1 h (wavelength of 365 nm, light intensity of 150 mW·cm -2 ), and after curing, it was dried in a vacuum oven at 60°C for 4 h, and the film was peeled off to obtain a self-healing network polymer electrolyte.
[0113] The room temperature conductivity of the self-healing network polymer electrolyte prepared in Comparative Example 1 is 9.7×10 -5 S cm -1 .
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A self-healing network polymer electrolyte, characterized in that: The preparation material comprises the following raw materials by weight: 3-10 parts of ionic liquid, 40-70 parts of polyethylene glycol diacrylate, 1-10 parts of disulfide diacrylate or diphenyl disulfide bis(2-methylacrylamide), 1-5 parts of crosslinking agent, 3-10 parts of chain extender, 1-5 parts of alkali, 20-30 parts of lithium salt, 1-10 parts of photoinitiator and 90-110 parts of solvent; The cross-linking agent and the chain extender both include thiol groups; The disulfide diacrylate is diphenyl disulfide bis(2-methylacrylate) or disulfide bis(2-methylacrylate); The crosslinking agent includes one or more of tetrakis(3-mercaptopropionate)pentaerythritol ester, hexa(3-mercaptopropionate)dipentaerythritol ester and trimethylolpropane tris(3-mercaptopropionate); The chain extender includes one or more of 3,6-dioxa-1,8-octanedithiol, 1,8-octanedithiol, 1,10-decandithiol, 1,4-butanedithiol, 1,2-ethanedithiol, 1,16-hexadecandithiol, 1,5-pentanedithiol and 1,6-hexanedithiol; The base includes one or more of n-butylamine, tert-butylamine, n-propylamine, tert-amylamine and isobutylamine; The method for preparing the self-healing network polymer electrolyte comprises the following steps: The ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate or diphenyl disulfide bis(2-methylacrylamide), a crosslinking agent, a chain extender, a lithium salt and a solvent are mixed, and then mixed with a photoinitiator and a base to obtain a precursor solution; The precursor solution is UV cured to obtain the self-healing network polymer electrolyte.
2. The self-healing network polymer electrolyte according to claim 1, characterized in that: The ionic liquid includes one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 2,3-dimethyl-1-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-1-methylpiperidinium bis(trifluoromethanesulfonyl)imide and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
3. The self-healing network polymer electrolyte according to claim 1, characterized in that: The photoinitiator includes one or more of 2,2-dimethoxy-2-phenylacetophenone, 4-methylbenzophenone and 1-hydroxycyclohexylphenyl ketone.
4. The self-healing network polymer electrolyte according to claim 1, characterized in that: The lithium salt includes one or more of LiPF6, LiClO4, LiTFSI, LiFSI, LiBOB and LiDFOB.
5. The method for preparing the self-healing network polymer electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: The ionic liquid, polyethylene glycol diacrylate, disulfide diacrylate or diphenyl disulfide bis(2-methylacrylamide), a crosslinking agent, a chain extender, a lithium salt and a solvent are mixed, and then mixed with a photoinitiator and a base to obtain a precursor solution; The precursor solution is UV cured to obtain the self-healing network polymer electrolyte.
6. The preparation method according to claim 5, characterized in that: The UV curing has an irradiation wavelength of 100-380 nm and an irradiation intensity of 10-200 mW·cm -2 , time is 0.5~10h.
7. Use of the self-healing network polymer electrolyte according to any one of claims 1 to 4 or the self-healing network polymer prepared by the preparation method according to claim 5 or 6 in polymer lithium batteries.
8. A polymer lithium battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the self-healing network polymer electrolyte according to any one of claims 1 to 4 or the self-healing network polymer prepared by the preparation method according to claim 5 or 6.
Citation Information
Patent Citations
Self-healing polymer and preparation method and application thereof
CN110437456A
Difunctional self-healing polymer electrolyte and preparation method thereof
CN110994020A